On the importance of nonlinear hydrodynamics and resonance frequencies on power production in multi-mode WECs. (December 2021) - Tran, N.; Sergiienko, N.Y.; Cazzolato, B.S.; Ding, B.; Wuillaume, P.-Y.; Ghayesh, M.H.; Arjomandi, M.
Abstract: Multi-mode Wave Energy Converters (WECs) are able to harvest energy from multiple Degrees-of-Freedom (DOFs) simultaneously, which increases the power that can be absorbed from the incident wave compared to single-DOF WECs. However, nonlinear coupling between hydrodynamic modes, which occurs when the WEC oscillates simultaneously in multiple directions, means that simply applying the typical control strategies used for single-DOF WECs can lead to sub-optimal performance. This study investigates the multi-DOF dynamic control of a submerged, flat cylindrical WEC subjected to hydrodynamic coupling effects modelled under the weakly nonlinear potential flow theory based on the weak-scatterer approximation. Results show that, at low incident wave frequencies, tuning the surge, heave and pitch modes of the WEC to the same natural frequency can result in power losses of up to 30% in the weakly nonlinear model compared to results obtained from a fully linear model. These discrepancies are attributed to the pitching motions of the WEC, which changes the projected surface area of the device relative to the equilibrium position and hence violates the assumptions of the linear theory. From these findings, a suggested design strategy where the surge, heave and pitch DOFs were all decoupled and tuned to different natural frequencies was therefore proposed. In the presence of weakly nonlinear hydrodynamic coupling, it was found that this design may result in significant improvements in power absorbed for the multi-mode WEC, compared to a case where all DOFs are simply tuned to match the peak frequency of a given sea state. Highlights: Nonlinear coupling between hydrodynamic modes greatly impacts multi-mode WEC power. Tuning the pitch, surge and heave modes to the same natural frequency reduces power. Tuning each mode to a different frequency may increase broadband power absorbed. Pitch changes the projected surface area, and hence power absorbed by other modes. Pitch should be tuned to a higher frequency to improve performance.